A meta-analysis of tumor necrosis factor-α and FAS/FASL polymorphisms with risk of pre-eclampsia. (2nd January 2019) - Lin, Yun; Wang, Lan; Yan, Yu; Zhou, Wei; Chen, Zhen
ABSTRACT: Previous observations investigated the association of tumor necrosis factor-α ( TNF-α), FAS and FASL polymorphisms with the risk of pre-eclampsia (PE). Conflicting results, however, were obtained. In this study, we aimed to evaluate the association between TNF-α −3 08 A/G, −850 C/T, −238 A/G, FAS −6 70 A/G, and FASL −844 C/T and PE risk using a meta-analysis. Pubmed, EBSCO, Embase, China National Knowledge Infrastructure, and Wanfang databases were searched up to April 10th 2018. Summarized odds ratios (ORs) with 95% confidence intervals (CIs) for the association between the five polymorphisms and PE risk were computed using a fixed or random effects model. The TNF-α −3 08 GA and GA/AA genotypes were associated with increased risks of PE in Asians (heterozygous comparison: OR = 2.68, 95% CI, 1.07–6.66; dominant model: OR = 2.70, 95% CI, 1.08–6.73) rather than in Caucasians. The FAS −670 AA genotype was associated with increased risks of PE in both overall analysis (heterozygous comparison: OR = 1.69, 95% CI, 1.17–2.45; homozygous comparison: OR = 2.47, 95% CI, 1.62–3.76; dominant model: OR = 1.91, 95% CI, 1.31–2.78; and recessive model: OR = 1.97, 95% CI, 1.35–2.87) and subgroup analyses. No significant association was found between TNF -α −850 C/T, −238 A/G and FASL −844 C/T polymorphisms and PE risk. These findings indicate that FAS −670 A/G polymorphism may be a susceptibility gene for the development of PE. Further genetic association studies with sufficient sample sizes are a research priority to confirm these findings.